Analisis Dampak Covid-19 pada Volume Transaksi Saham dan Harga Saham: Studi Kasus Pada Kelompok Perusahaan Transportasi yang Terdaftar di BEI Tahun 2020 - Br Perangin-angin, Siska; Siburian, Nelsi Agustina; Nst, Rivaldi Ahmad; Batubara, Maryam (ManBiz: Journal of Management and Business, 2024)
The reason for this study was to decide the effect of Coronavirus on stock exchange volume and stock costs. The object of this exploration is a gathering of transportation organizations recorded on the Indonesia Stock Exchange in 2020. The populace in this study is 42 transportation organizations. What's more, the example utilized is upwards of 20 organizations. This study utilizes optional information. The information examination strategy utilized in this exploration is elucidating subjective information examination method. The consequences of this study demonstrate that the volume of stock exchanges and costs impacted by the COVID-19 pandemic diminished, upwards of three organizations, including area, air and ocean transportation, which encountered a decay. What's more, that accomplished an increment upwards of 4 organizations, remembering ocean transportation organizations and land transportation organizations for delivery administrations.